2012
DOI: 10.1089/nat.2011.0328
|View full text |Cite
|
Sign up to set email alerts
|

Short Double-Stranded RNA with Immunostimulatory Activity: Sequence Dependence

Abstract: Small interfering RNAs (siRNA) are able to activate the mammalian innate immune system depending on their structure, sequence, and method of delivery. The immunostimulatory activity of double-stranded RNA can be applied to antiviral and antitumor therapy. Here we identified a set of 19-bp RNA duplexes with 3-nucleotid overhangs in the 3' ends that display immunostimulating activity (here and after immunostimulating RNA, or isRNA) and studied their sequence/activity relationships. It was found that the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…Although the control type 1 interferon inducer poly(I:C) [27] activates the synthesis of IFN-α more effectively than isRNA, it induces as high as an 17-fold increase of IL-6 level (Figure 1B). The data obtained are in agreement with our previous results [25] demonstrated that isRNA after intravenous administration mainly induces the synthesis of IFNα and to a lesser extent the synthesis of IL-6. It should be noted, that after i.p.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Although the control type 1 interferon inducer poly(I:C) [27] activates the synthesis of IFN-α more effectively than isRNA, it induces as high as an 17-fold increase of IL-6 level (Figure 1B). The data obtained are in agreement with our previous results [25] demonstrated that isRNA after intravenous administration mainly induces the synthesis of IFNα and to a lesser extent the synthesis of IL-6. It should be noted, that after i.p.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we used the most effective among previously tested [25] immunostimulatory isRNA molecules of 19-bp long with 3-nt overhangs at the 3′-ends. As the positive control, poly(I:C), which is known to induce an interferon response, was used [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations